Intertwined : Resonance, Affect, and Resistance in Open-Form Music–Dance Performance - Schacher, Jan (mdwPress, 2026)
This chapter explores how sounding and moving mirror each other, how dancers and musicians rely on the same perceptual and affective phenomena. And equally, how for the viewer and listener, being connected to the performers is through a phenomenon of corporeal resonance. Beyond the idiomatic elements of dance and music, intentions are transmitted through common bodily patterns. The artist’s inner states are completed and reconstructed by audiences and co-performers. The key element enabling the connection is Resonance, an intertwining in mutual adaptive oscillations by impulses, phrases, actions, and perceptions. Resistance appears as a necessary catalyst and effort generator for heightened awareness states and tensions that contribute to a transformative performance. Pushing with body against body, through an ecological, embodied relation, the self, its agency, and the perception of time condense into a complex manifold that is negotiated by performers and audience alike.
Keywords: musiikin esittäminen; ruumiillisuus; tanssi